Síntese e caracterização do LiAlSi2O6 por novas rotas de produção - Lima, Hestia Raissa Batista Reis (2013)
The spodumene (LiAlSi2O6 - LAS) is a silicate that has shown good results for high-dose dosimetry for gamma rays. This silicate may be obtained naturally or synthetically. The synthetic spodumene has been produced by solid state reaction, whose difficulty arises from the need to employ high temperatures. This paper aims to produce LAS through two different production routes: the proteic sol-gel and Pechini methods. The material produced was characterized by X-ray diffraction (XRD), differential thermal analysis (DTA) and thermogravimetry (TGA) in order to evaluate the structural properties of the material, as well as possible changes in physical or chemical properties depending on the temperature. It was found by XRD and Rietveld refinement was possible to obtain LAS B-spodumene phase by both methods. The thermal analysis showed that the material for both methods suffer considerable loss of weight in the temperature range 20-600 °C. Through thermoluminescent measures, one can observe that the LAS produced by both methods shows thermoluminescent peaks from beta irradiation at a dose of 1 Gy, thus allowing its application dosimetry. It can be concluded therefore that there is the possibility of producing them in large numbers at reduced cost and environmental impact, being viable in dosimetry. It also follows that the sol-gel protein appeared to be the best way to produce the LAS compared with other routes used, such as solid state synthesis or devitrification.